Individual and Environmental Correlates of Adolescents’ Moral Decision-Making in Moral Dilemmas - Bacchini, Dario; De Angelis, Grazia; Dragone, Mirella; Esposito, Concetta; Affuso, Gaetana (Frontiers in Psychology, 2021)
While extensive research has been conducted on adults’ judgments in moral sacrificial dilemmas, there is little research with adolescents. The present study aimed at: i) adding further empirical evidence about adolescents’ moral decisions (deontological vs. utilitarian) in sacrificial moral dilemmas, and ii) investigating how these moral decisions relate with gender, school grade, emotional traits (callous-unemotional traits), context-related experiences (perceived parental rejection and community violence exposure), and moral-related factors (moral disengagement and universalism value). A sample of 755 Italian adolescents (54.7% females; Mean age = 16.45, S.D. = 1.61) attending the second and the fifth year of the secondary school took part in the study. Two sacrificial trolley-type dilemmas (where harmful actions promote the greater good) were presented. In the “switch” scenario (impersonal sacrificial dilemma), the choice is whether to hit a switch to save five people killing only one person. In the “footbridge” scenario (personal sacrificial dilemma), the choice is whether to push a fat man off a footbridge saving five persons. For each scenario, participants had to indicate whether the proposed action was “morally acceptable” or not. Data were analyzed performing Generalized Linear Mixed Models. Our results showed that: i) adolescents were more likely to indicate as admissible to hit the switch rather than to push the fat man; ii) males and younger adolescents were more likely to say it was morally acceptable to intervene both in the switch and the footbridge situations, compared to females and older adolescents, respectively; iii) higher levels of callous-unemotional traits, perceived parental rejection, and moral disengagement, on the one hand, and lower levels of universalism, on the other hand, were associated to higher admissibility to intervene in the footbridge scenario. Higher community violence exposure was associated to a lower propensity to intervene in the switch scenario. Overall, the present study expands the research on sacrificial dilemmas involving a sample of adolescents. The findings support previous studies concerning the role of emotions in making moral decision but, at the same, open new perspectives regarding the role of contextual experiences and moral-related factors.